(untitled) (Law and world, 2015)
The article presents the legal status of women in Georgia. It is known that in Georgian family the man had ruling, privileged positi on compared to woman. His words had the force of law and each family member unconditi onally obeyed any his decision. According to both Georgian and customary law a woman should be humble, obedient to her husband and complaisant. A woman should incur her obligati ons to her husband not only during her lifeti me but aft er his death. Namely, she was not allowed to marry for a second ti me if she had children. As well she was not allowed to marry in the same village or to the same surname which his husband belonged to.